INTERNALISASI NILAI-NILAI KARAKTER DALAM PEMBELAJARAN IPS PADA SISWA SMP NEGERI MODEL TERPADU BOJONEGORO - Eko Prasetyo Utomo (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2020)
The focus of this study is to explore the process of internalizing the character values in social studies learning in students with aspects of the internalization process includes first identifying character values in social studies learning on students and second-niali identify meaning internalization of the character values in social studies learning. This study used a qualitative approach with a phenomenological research design. The results of this study indicate that the first internalization of the values of character is essentially a process of cultivation of character values into one's self so that these values become part of him, animating mindset, attitude, and behavior and build self-awareness to apply the value the value. Second values are internalized characters in three stages or phases representing the internalization process that phase transformation of values, stages of the transaction value, and the last stage trans internalization. The process of internalization of character values in social studies learning by example and practice activities teachers direct learning experiences through learning model, learning methods, learning materials, and evaluation. Behavior characterized actualized by students of SMP Negeri Model Terpadu Bojonegoro in everyday life in a social studies lesson in class that is disciplined, honest, likes to read, care for the environment, tolerance, social care, friends/ communicative responsibility.